Round table discussion: the role of Inspection in the educational innovation - Esteban Frades, Santiago; Sarasúa Ortega, Avelino; Serentill Rubio, Josep; Zulueta Castañeda, Manuel (Avances en Supervisión Educativa, 2016)
A summary of the round table discussion developed in The Congress of Education Inspectors held in October 2016 in Valladolid.The main ideas that were discussed were how throughout the history of the Inspectors have always been involved in innovation and how the "White Paper of the teaching profession and its School environment" is that the inspection becomes a significant agent of the educational change. A methodological change is urgently needed in classrooms and centers with a work by competencies, the inspection should, through control and supervision, verify that these innovations are being carried out.That paradigmatic change that is being happening in the educational field requires a rethinking of the inspection functions and the new role that inspectors must assume, taking into account that there are different inspections in Europe that are already changing the model.Some Autonomous Regions are publishing innovation rules and granting inspection to their monitoring and evaluation systems. There are three possible and compatible models of performance of the innovative inspection: one, based on the control and supervision so that apply the rule that makes innovation possible; another, which is to enable the pedagogical autonomy of the centers; And the third model of collaboration and involvement in the innovation of the centers.It is dangerous for inspection to be dedicated only to the main functions are those of control and supervision and avoid oversaturation of many actions that are not his own. There must be a leadership and coordination on the part of the inspection of educational services that involve the centers, but points out the danger that this may dilute the inspection role. The inspection would have to have more pedagogical training in order to do their job well and have more influence in the centers and the faculty.
Keywords: inspection; education; innovation; supervision; advice and evaluation